Study and Optimization of a Hybrid Power Generation System to Power Kalakala, a Remote Locality in Northern Côte d'Ivoire - Koffi, Jules Yao; Sako, Koita Mohamed; Koua, Blaise Kamenan; Koffi, Paul Magloire Ekoun; Nguessan, Yao; Diango, Alphonse Kouadio (International Journal of Renewable Energy Development, 2022)
This work presents the results of a study to optimize the production of electricity, by hybrid system Photovoltaic – Diesel – Batteries, to power the village of Kalakala in the north of Côte d'Ivoire. The study site is an isolated rural community, powered by a diesel generator. It is located in northern Côte d'Ivoire. HOMER software has been used for system simulation and optimization. The result of this study is then compared to those of PV - Batteries and diesel alone systems. From the results of the simulations, it appears that the optimal combination of the hybrid system includes a diesel generator of 50 kW, a photovoltaic field of 46 kW, 10 batteries of 48V and a converter of 100 kW. With a photovoltaic penetration rate of 52.7%, this system, compared to the photovoltaic - batteries system, reduces the photovoltaic field by 56%, the number of batteries by 61.5% and increases battery life by 42.84%. Compared to diesel alone, it reduces fuel consumption and the quantity of CO2 by 60% and improves diesel efficiency by 17%. The cost of generating electricity for the hybrid system is €0.373/kWh compared to €0.466 and €0.608/kWh respectively, for the PV-Batteries and diesel alone systems. The hybrid system with the best technical, economic and environmental performance could be a good alternative for generating electricity in remote communities.